Iraqi brain drain-motives and consequences - Khudheir, Huda Yahya (KDI School, 2011)
This thesis examines Iraq experiencing brain drain, and government's policies in dealing with this phenomenon. The consequences assert the key role of government in improving economic status in the country, a matter that helps Iraqi brains, who earned PhDs abroad, make their choices whether to stay or return home. However, this study points out some analysis about security conditions that affect the migrated brains. And it proposes the idea of imitation as an essential factor in brains' choice. Thus, Iraqi government needs to imitate a successful experience, like Korean policy concerning this issue. The Iraqi government's policy is to regain the brains through adopting different strategies and incentives. Yet, the Iraqi policy procedures still need more to be done.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Iraq